2019
DOI: 10.5858/arpa.2017-0475-ra
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Challenges in Colorectal Cancer Reporting

Abstract: Context.-Pathologic assessment of colorectal cancer resection specimens plays an important role in postsurgical management and prognostication in patients with colorectal cancer. Challenges exist in the evaluation and reporting of these specimens, either because of difficulties in applying existing guidelines or related to newer concepts.Objective.-To address challenging areas in colorectal cancer pathology and to provide an overview of the literature, current guidelines, and expert recommendations for the han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 165 publications
(164 reference statements)
0
33
0
2
Order By: Relevance
“…The survey was designed to focus on issues regarding pT and pR staging of CRC (Table 1; Figure 1). The survey did not include the controversial topics of isolated tumour cells in nodes and defining extramural tumour deposits (EMTDs), because these were being assessed elsewhere during the study period and/or had already been considered in recent publications 5–7 . The survey included 15 staging scenarios grouped into five sections, and three questions about the respondent's occupation characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was designed to focus on issues regarding pT and pR staging of CRC (Table 1; Figure 1). The survey did not include the controversial topics of isolated tumour cells in nodes and defining extramural tumour deposits (EMTDs), because these were being assessed elsewhere during the study period and/or had already been considered in recent publications 5–7 . The survey included 15 staging scenarios grouped into five sections, and three questions about the respondent's occupation characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly Joseph et al [46] found that better LN harvests improve cancer survival irrespective of patients' nodal statuses (N1 or N0). Tumour-host interactions may be a plausible explanation for this, as higher LN yield may reflect a stronger host immune response [47].…”
Section: Limitationsmentioning
confidence: 99%
“…Interestingly Joseph et al [47] Found that improvement in colorectal cancer survival was associated with greater LN harvest irrespective of patients' nodal statuses (N1 or N0). Tumour-host interactions may be a plausible explanation for this, as higher LN yield may re ect a stronger host immune response [48].…”
Section: Limitationsmentioning
confidence: 99%